Locally adapted planting basin technology to ameliorate impact of drought (low and variable rainfall) on crop yield and tree survival - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
Implemented using planned comparisons with performance measurement across >3,500 farmers in three counties in Kenya, four woredas (districts) in Ethiopia, and in Mali